Characterization and classification of cassava flour produced in Barreirinhas, Maranhão - Alves Junior , James Pereira; Barbosa , Sarah Dalila Mendes; Amorim, Ester Evelyn Barros Diniz; Ferreira, Gabrielly Santos; Menezes, Letícia Bianca Gouveia; Silva, Tonicley Alexandre da; Rodrigues, Daniele Gomes Cassias; Pinto, Nísia Andrade Villela Dessimoni; Souza, Poliana Mendes de (Food Science and Technology, 2025)
Cassava flour is a strategic food for Brazilian food security due to its low cost, good acceptance, and versatility, as well as the cultural custom of consumption, especially in the North and Northeast regions. However, as in Barreirinhas, Maranhão, its artisanal production lacks standardization and sanitary control. This study aimed to characterize and classify nine samples of artisanal flours sold and produced in Barreirinhas, based on physical, physicochemical, and microbiological analyses. The classification followed Normative Instruction 52/2011 of the Brazilian Ministry of Agriculture, Livestock, and Supply. The present study revealed significant differences in the acidity levels between the dry and water flour groups, 1.87 and 1.32 meq NaOH 0.1 N 100 g−1, respectively, and reinforced the non-uniformity in the parameters evaluated between the groups. Principal component analysis explained 70.3% of the total variance. Two samples had Bacillus cereus above the legal limit (1.0 × 10⁴ and 1.5 × 10⁴ colony-forming unit g−1), and four had a high load of molds and yeasts (> 10³ colony-forming unit g−1). Total coliforms were detected in two samples (23 most probable number g−1), while Salmonella spp. was absent and Escherichia coli was under 3 most probable number in all samples. The results show variations in quality and reinforce the need to train producers and adopt good manufacturing practices to guarantee food safety and strengthen the traditional production chain.